Correction: Recombinant NAD-dependent SIR-2 protein of Leishmania donovani: immunobiochemical characterization as a potential vaccine against visceral leishmaniasis. - Rajendra K Baharia; Rati Tandon; Tanuj Sharma; Manish K Suthar; Sanchita Das; Mohammad Imran Siddiqi; Jitendra Kumar Saxena; Shyam Sundar; Anuradha Dube (Public Library of Science (PLoS), 2015)
[This corrects the article DOI: 10.1371/journal.pntd.0003557.].